PTH-124 Changes In The Indications For Referral Of Adults For Intestinal And Multivisceral Transplantation. (9th June 2014) - Rutter, C; Sharkey, L; Butler, A; Russell, N; Gabe, S; Jamieson, N; Woodward, J; Duncan, S; Bond, D; Green, J; Middleton, S
Abstract : Introduction: Small bowel transplantation (SBT) was first performed in the UK in Cambridge in 1991. Recipients mow undergo small bowel (SBT), liver and small bowel (LSBT), modified multivisceral (MMVT – small bowel, stomach, pancreas, no liver) and multivisceral (MVT – intestine, stomach, pancreas and liver) transplantation. Cambridge is the only UK centre offering MVT in adults. The main indications for referral to a transplant centre are: Irreversible intestinal failure plus life threatening complications of parenteral nutrition (PN). Extensive surgery requiring partial or complete evisceration. Methods: Prospective data was collected from all patients who underwent intestinal and multivisceral transplantation at Addenbrooke's Hospital between 2003 and 2013. All patients are discussed and indications for transplantation agreed prior to listing at NASIT (National Adult Small Intestinal Transplant forum). Results: 47 transplants were performed on 43 patients; 4 procedures (9%) were re-transplantation for a primary non-functioning graft (2/4) or acute rejection (2/4). The indications for transplant are presented below: Sixteen transplants were performed in 2013 - MVT (57%), SBT (31%), LSB (6%) and MMVT (6%). 50% of these were due to short bowel - arterial ischaemia (50%), Crohn's (26%), venous ischaemia (12%) and other short bowel (12%). Colon is now routinely included in the graft to aid fluid balance and does not preclude endoscopic surveillance for rejection. Conclusion: The number of small bowel and multivisceral transplants performed over the last 10 years has increased, and more than doubled in 2013. Short bowel remains the commonest indication for transplantation. Historically this was mainly due to Crohn's disease however in 2013, it was mainly due to ischaemia; this trend was reflected worldwide. In our cohort, an increase in acute arterial thromboses causing coeliac/mesenteric ischaemia resulted in 3 recipients being listed urgently for MVT. There has also been an increase in the number of patients referred with portal vein thromboses extending into the superior mesenteric vein, precluding liver transplant alone. Disclosure of Interest: None Declared.